Prospective longitudinal study of children with tic disorders and/or obsessive-compulsive disorder: relationship of symptom exacerbations to newly acquired streptococcal infections - Luo, Feng; Leckman, James F; Katsovich, Liliya; Findley, Diane; Grantz, Heidi; Tucker, Daniel M; Lombroso, Paul J; King, Robert A; Bessen, Debra E (Pediatrics (Evanston), 2004)
It has been proposed that infection by group A beta-hemolytic streptococci (GABHS) can trigger acute symptom exacerbations among patients with Tourette's syndrome (TS) or obsessive-compulsive disorder (OCD), via autoimmune mechanisms. To examine the temporal relationship between newly acquired GABHS infections (and other immunologic indices) and acute exacerbations of tics and obsessive-compulsive symptoms. Pediatric patients (7-17 years of age) with TS and/or OCD (N = 47) and healthy control subjects (N = 19) were prospectively monitored for newly acquired GABHS infections, nonspecific markers of acute inflammatory responses, and D8/17-reactive cells (a marker of rheumatic fever). Objective monthly ratings of tic and obsessive-compulsive symptom severity were used to determine the timing of symptom exacerbations. The overall rate of acute exacerbations of neuropsychiatric symptoms was 0.56 exacerbations per patient per year. The average rate of new GABHS infections, using a stringent definition, was 0.42 infections per subject per year among patients, compared with 0.28 infections per subject per year for control subjects. The association between symptom exacerbations and new GABHS infections among patients was no greater than that expected on the basis of chance. At baseline, patients demonstrated significantly higher levels of D8/17-reactive cells and neopterin, compared with control subjects, but there was no consistent pattern of change when exacerbation time points were compared with baseline or follow-up time points. The results suggest no clear relationship between new GABHS infections and symptom exacerbations in an unselected group of patients with TS and/or OCD.